BASAL CELL CARCINOMA IN XERODERMA PIGMENTOSUM IN AN 18.YEAR.OLD MALE - Satya Wydya Yenny; Frien Refla Syarif (Majalah Kedokteran Andalas, 2014)
Xeroderma pigmentosum (XP) is a rare autosomalrecessiye disorder that occurs becauseof inactivation of the xeroderma pigmentosum protein, which is an important DNA damagerecognition protein involved in DNA nucleotide excision repair (NER). This defect, whichprevents removal of a wide array of direct and indirect DNA /esions, is assocrafe d with adecrease in catalase activity. This photosensifive disarder resulfs in multipte face, neck andhead basal cell carcinomas (BCCs), squamous cell carcinomas (SCCsJ and melanomas whichis characterized by cellular hypersensitivity to ultraviolet radiation, development of cancers at anearly age, severe actinic cancer, and photophobia. As a common sfressor of skin, uttraviotet-B(UVB) induces a biphasic HIF-Iq variation through ROS generation in keratinocytes. Wereported a case of an 18-year-old-male with XP presented with BCC on the teft cheek. Thcpatient had hypo- and hyperpigmented macules since early childhood, throughout the body,more on sun exposed areas.AbstrakXeroderma pigmentosum (XP) adalah kelainan autosomal resesif yang jarang terjadidisebabkan oleh inaktivasi protein xeroderma pigmentosum yang merupakan protein pentingpengenal kerusakan DNA yang terlibat dalam nucleotide excision repair (NER) DNA. Defekini mencegah penghapusan beragam lesi DNA langsung dan tidak langsung, terkait denganpenurunan aktivitas katalase. Kelainan fotosensitivitas ini menyebabkan terjadinya basalkarsinoma sel (BCC), karsinoma sel skuamosa (SCC) dan melanoma pada wajah, leher dankepala yang ditandaidengan hipersensitivitas seluler radiasi ultraviolet, perkembangan kankerpada usia dini, kanker actinic yang berat, dan fot'ofobia. Ultraviolet-B (UVB) merupakan stressorpada kuit yang menginduksi variasi HIF-1q bifasik melalui generasi ROS dalam keratinosit.Kami melaporkan kasus XP dengan BCC di pipi kiri pada laki-laki berusia 18 tahun. Pasienmemiliki makula hipo- dan hiperpigmentasisejak masa kanak-kanak awal, seluruh tubuh, lebihpada daerah yang terpapar sinar matahari.